Maternal near miss: a retrospective study in a tertiary care hospital at South India - Sengodan, Subha Sivagami; Mallesh, Tejashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: A maternal near miss (MNM) case is defined as a woman who nearly died but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy. MNM situations tend to mirror the causes of maternal death. Hence, review of these cases has been found to help in the assessment of maternal health services. These cases are called as MNM or severe acute maternal morbidity (SAMM) and auditing these cases is called near miss audit (NMA). Methods: A retrospective study of 201 MNM cases over a period of 12 months from January 2023- December 2023. Demographic data were collected from MNM review form and records. Data studied and analyzed. Results: There were 11,340 deliveries and 11,126 live births during the study period out of which 201 MNM cases were studied. Haemorrhage followed by anemia was the most common cause of near miss events. The most common age group affected in the near miss cases in the present study was 20 to 35 years (80%). Majority of the cases were referred from the nearby PHCs and government hospitals. Conclusions: Most maternal deaths are preventable by optimal utilization of existing MCH facilities, identifying the bottleneck in health delivery system, early identification of high-risk pregnancy and therein timely referral to tertiary care centre.